The colonization of different lupine taxon (Lupinus spp.) by Macrosiphum albifrons Essig, 1911 in Minsk region, Belarus - Zhorov, Dmitrii G.; Anokhina, Vera S.; Ramanchuk, Irina Y. (Experimental Biology and Biotechnology, 2018)
The paper presents data about condition of different species and forms of lupine (Lupinus spp.) by lupine aphids (Macrosiphum albifrons Essig, 1911). The dependence of aphids abundance on the quantitative content of alkaloids in plant leaves are given. It is found that lupine yellow has a low degree of population (1.8 points) as compared to the blue lupine (3.2 points), and other forms.
Keywords: Aphidoidea; Fabaceae; Lupinus spp.; invasive species; alkaloids; lupine varieties; the degree of colonization; Belarus